Docência nos anos iniciais do ensino fundamental: é possível dialogar sobre gênero na escola? - Faria, Cássio Rodrigues (2023)
Linked to the Research Line “Knowledge and Educational Practices” of the Graduate Program in Education at the Federal University of Uberlândia (PPGED/UFU), as well as to the Research Group Education, Sexualities and Performativities (GPESP), the present study, in master's level, aimed to understand the challenges that teachers in the Early Years of Elementary School have to address issues related to gender with students. Thus, as a research locus, we analyzed reports about the educational practice of a group of teachers from a school in the interior of the State of Minas Gerais, approaching what are the perspectives and challenges that it encounters in approaching the gender theme. Based on post-structuralist studies and their interfaces with the dynamics of educational work, we set out for an exploratory research with a qualitative approach. The instruments for data generation were the application of the questionnaire and conducting semi-structured interviews. As a result, the present study showed that the teachers are insecure in working with the concept of gender; they have difficulties to define the concept of gender based on post-structuralist studies; most of the participants reinforced that there is a possibility of dialogue with the male and female students during the educational work, focusing on the (re)production of gender as a mechanism for promoting inequalities and valuing differences; there is no direction from the field school for the study of gender; lack of public policies to support the school in dialogue with the school community; there are sociocultural and religious barriers organized within the structure of the school community and they often trigger the silencing of discussions within the teaching programmatic content and parallel to this, the fear of reprisals, violence and persecution of teachers who promote the discussion within the school.